2015
DOI: 10.1155/2015/957925
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations on Characteristics of Stresses in U-Shaped Metal Expansion Bellows

Abstract: Metal expansion bellows are a mechanical device for absorbing energy or displacement in structures. It is widely used to deal with vibrations, thermal expansion, and the angular, radial, and axial displacements of components. The main objective of this paper is to perform numerical analysis to find various characteristics of stresses in U-shaped metal expansion bellows as per the requirement of vendor and ASME standards. In this paper, extensive analytical and numerical study is carried out to calculate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The development of plastic hinges formed on the crown and the corrugation root induces the columnar deformation through some mechanism for both internal and external pressures [21]. Circumferential membrane stresses found very lower than meridional stresses under axial internal pressure [22,23]. Numerical methods, in general, are adopted to find out mechanical parameters such as stiffness and displacements, and formulas are applicable when the Poisson ratio, µ ˂ 0.5.…”
Section: Location Of Tangential Membrane Stress (S 1 )mentioning
confidence: 99%
“…The development of plastic hinges formed on the crown and the corrugation root induces the columnar deformation through some mechanism for both internal and external pressures [21]. Circumferential membrane stresses found very lower than meridional stresses under axial internal pressure [22,23]. Numerical methods, in general, are adopted to find out mechanical parameters such as stiffness and displacements, and formulas are applicable when the Poisson ratio, µ ˂ 0.5.…”
Section: Location Of Tangential Membrane Stress (S 1 )mentioning
confidence: 99%
“…The study and analysis on characteristics of stress can be found in the further papers [3]. The analysis of an axial bellow expansion joint at elevated temperature has been carried out in [4] using theory of contact modelling. Igi [5] proposed a double convolution bellows to reduce excessive deformations due to heat expansion, vibration, nonuniform subsidence of ground, etc., whereas Newland [6] studied buckling analysis of corrugated bellows expansion joints subjected to internal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [8] have investigated the effect of environmental medium on fatigue life for U-shaped bellows expansion joints. Gawande et al [9] have carried out extensive analytical and numerical study to calculate the different characteristics of stresses due to internal pressure varying from 1MPa to 2MPa in U-shaped bellows. Finite element analysis by using ANSYS 14 is performed to find characteristics of U-shaped metal expansion bellows.…”
Section: Introductionmentioning
confidence: 99%
“…Gawande et al [1] have developed the mathematical model for axial natural frequency of bellows, He has performed the numerical and modal analysis for natural frequency of axial vibration of metal expansion bellows and compare the analytical results with experimental results. From the literature survey, it is seen that number of researchers have worked on study and applications of different types of bellows under various working conditions, their comparison, manufacturing processes and few are working on fatigue life enhancement [9]. But investigations on need for selection of proper material of bellow for given application, their proper design, stresses induced, fatigue life analysis, prediction of failure, investigations on various characteristics of different bellows and vibration effect is essential.…”
Section: Introductionmentioning
confidence: 99%